The involvement of sirtuin 1 and heme oxygenase 1 in the hepatoprotective effects of quercetin against carbon tetrachloride-induced sub-chronic liver toxicity in rats - Kemelo, Mighty Kgalalelo; Pierzynová, Aneta; Kutinová Canová, Nikolina; Kučera, Tomáš; Farghali, Hassan (Chemico-biological interactions, 2017)
The present study was designed to evaluate the therapeutic potential of quercetin in a sub-chronic model of hepatotoxicity. The roles of putative antioxidant enzymes, sirtuin 1 (SIRT1) and heme oxygenase 1 (HO-1), in hepatoprotection were also addressed. Sub-chronic liver injury was induced in rats by intraperitoneal administration of 0.5 ml/kg carbon tetrachloride (CTC), once every 3 days, for 2 weeks. Some CTC rats were concurrently treated with 100 mg/kg quercetin, intragastrically, once every day, for 2 weeks. The effects of these drugs in the liver were evaluated by biochemical, histological, immunohistochemical and molecular biological studies. CTC triggered oxidative damage to the liver as unanimously shown by altered biochemical parameters and liver morphology. Furthermore, CTC highly upregulated HO-1 and SIRT1 expression levels. Concomitant treatment of rats with quercetin downregulated SIRT1 expression and ameliorated the hepatotoxic effects of CTC. However, quercetin did not have any significant effect on HO-1 expression and bilirubin levels. Collectively, these results suggest that the antioxidant and cytoprotective effects of quercetin in CTC treated rats were SIRT1 mediated and less dependent on HO-1. Thus, pharmacologic modulation of SIRT1 could provide a logic therapeutic approach in sub-chronic hepatotoxicity.
Keywords: Liver; Animals; otrava chloridem uhličitým; Alanine Transaminase; Bilirubin; Aspartate Aminotransferases; Sirtuin 1; quercetin; alanintransaminasa; Rats, Wistar; játra; Up-Regulation; Immunohistochemistry; upregulace; Protective Agents; imunohistochemie; hemoxygenasa-1; Down-Regulation; aspartátaminotransferasy; Male; bilirubin; krysa rodu Rattus; Heme Oxygenase-1; Carbon Tetrachloride Poisoning; down regulace; Quercetin; zvířata; mužské pohlaví; ochranné látky; Rats; sirtuin 1; potkani Wistar